Enabling Eco-Cities Defining, Planning, and Creating a Thriving Future (Springer Singapore, 2018)
Cities are striving to become more resilient, adaptive and sustainable; this requires new ways of governing and developing the city. This book features chapters by researchers using regenerative development and transitions theories to envisage how Eco-Cities could be planned, designed and created, and concludes with practical tools and an outline of how this evolution could be facilitated. It examines two major questions: How can we use understandings of Eco-Cities to address the legacy of urban built form and existing practices which often make it difficult to create the systemic changes needed? And what are the elements of complex urban places and spaces that will enable the planning, creation and evolution of thriving cities? The book will appeal to planners, city makers, urban researchers, students and practitioners, including planners, designers, architects and sustainability managers, and all those seeking to envisage the steps along the path to thriving cities of the future.